LIVING QUR’AN DAN HADIS DALAM PRAKTIK DAKWAH KULTURAL MUHAMMADIYAH (Studi Kasus Pagelaran Wayang Jelang Ramadan di Yogyakarta) - Muhammad Ridha Basri (Al-Mufassir: Jurnal Ilmu Alquran, Tafsir dan Studi Islam, 2023)
As a symbolic universe, Islamic religious texts in the form of the Qur'an and hadith are not only meant to be read and interpreted (informative function), but also to live within society (performative function). This study explores the phenomenon of the living Qur'an and hadith within the local Muhammadiyah community, an organization often labeled as anti-cultural. In 2002, Muhammadiyah developed the concept of cultural da'wah, which incorporates culture as a strategy for da'wah and provides space for cultural expression. This article examines the phenomenon of welcoming Ramadan 1438 Hijriah by the Tamantirto Muhammadiyah Branch in Yogyakarta, who performed a wayang play titled Wahyu Makutharama. This study found that the wayang performance, combined with Quranic recitations, served as a medium for da'wah, fostering ukhuwah, and providing spiritual recreation. During the performance, verses from the Qur'an were recited, and religious values derived from hadith texts regarding welcoming Ramadan, the qualities of a leader, and the obligation to seek knowledge were conveyed.